CRYSTAL MOLDS ON MARS: MELTING OF A POSSIBLE NEW MINERAL SPECIES TO CREATE MARTIAN CHAOTIC TERRAIN - Peterson R.C.; Wang R. (My University, 2006)
Images sent back by the Mars Exploration Rover Opportunity from the Meridiani Planum show sulfate-rich rocks containing plate-shaped voids with tapered edges that are interpreted as crystal molds formed after a late-stage evaporite mineral has been removed. Experimental studies of the MgSO4-H2O system at low temperatures reveal that the tri-clinic phase MgSO4·11H2O exhibits a crystal morphology that matches the shapes of these molds. MgSO4·11H2O melts incongruently above 2 °C to a mixture of 70% epsomite (MgSO4·7H2O) and 30% H2O by volume. When this occurs while crystals are encased in sediment, plate-shaped voids remain. The existence of ice, low surface temperatures, and the high sulfate content of surface rocks and soil on Mars makes MgSO4·11H2O a possible mineral species near the surface at high latitudes or elsewhere in the subsurface. If an evaporite layer contained a significant amount of this phase, incongruent melting would result in a rapid release of a large volume of water and could explain some of the landform features on Mars that are interpreted as outflow channels. MgSO4·11H2O would not survive a sample return mission unless extraordinary precautions were taken. © 2006 Geological Society of America.
Keywords: EPSOMITE; INCONGRUENT MELTING; MARS; MINERALOGY; SULFATE